2017
DOI: 10.1155/2017/5904361
|View full text |Cite
|
Sign up to set email alerts
|

Oral Administration of Tualang and Manuka Honeys Modulates Breast Cancer Progression in Sprague‐Dawley Rats Model

Abstract: Breast cancer has been recognized as the leading cause of death in women worldwide. Research has shown the importance of complementary and alternative therapies in cancer. In this study, we investigated the antitumoural therapeutic effects of Malaysian Tualang honey (TH) and Australian/New Zealand Manuka honey (MH) against breast cancer in rats. Thirty syngeneic virgin female Sprague-Dawley (SD) rats were induced by the carcinogen 1-methyl-1-nitrosourea (MNU) 80 mg/kg. The treatment started when first palpable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 41 publications
7
61
0
Order By: Relevance
“…It was demonstrated a reduction of tumor growth, tumor grading, estrogenic activity, and hematological parameters. In addition, an increase in the expression of pro-apoptotic proteins, such as Caspase 9 and p53, and the involvement of some proteins of the inflammation pathway, such as TNF-α and COX-2 have been demonstrated [ 72 ].…”
Section: Honey and Health And Diseasesmentioning
confidence: 99%
“…It was demonstrated a reduction of tumor growth, tumor grading, estrogenic activity, and hematological parameters. In addition, an increase in the expression of pro-apoptotic proteins, such as Caspase 9 and p53, and the involvement of some proteins of the inflammation pathway, such as TNF-α and COX-2 have been demonstrated [ 72 ].…”
Section: Honey and Health And Diseasesmentioning
confidence: 99%
“…It ameliorated the intrinsic apoptotic pathway through upregulation of the expression of proapoptotic proteins such as caspase-9, APAF-1 (apoptotic protease activating factor 1), p53, IFN- γ (interferon gamma), and IFNGR1 (interferon gamma receptor 1). Concomitantly, honey was found to downregulate the expression of antiapoptotic proteins such as Bcl-xL (B-cell lymphoma extra large), TNF- α , COX-2, E2 (estrogen), and ESR1 (estrogen receptor 1) [ 149 , 150 ]. It was also demonstrated that honey alone induces intrinsic or caspase-9 apoptotic pathway with no evidence of the involvement of extrinsic or caspase-8 pathway [ 149 , 150 ].…”
Section: Medicinal Effects Of Honey and Mechanisms Of Actionmentioning
confidence: 99%
“…Concomitantly, honey was found to downregulate the expression of antiapoptotic proteins such as Bcl-xL (B-cell lymphoma extra large), TNF- α , COX-2, E2 (estrogen), and ESR1 (estrogen receptor 1) [ 149 , 150 ]. It was also demonstrated that honey alone induces intrinsic or caspase-9 apoptotic pathway with no evidence of the involvement of extrinsic or caspase-8 pathway [ 149 , 150 ]. Flavonoids and phenolic contents of honey have been encountered to occlude the cell cycle of glioma [ 145 ], melanoma [ 146 ], colon [ 40 ], and cancer cell lines in G0/G1 phase.…”
Section: Medicinal Effects Of Honey and Mechanisms Of Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 (4): 1549-1558(2020 histopathological changes with underlying pathological processes helps to interpret the results accurately. Study shows that crude form of Tualang Honey (TH) and Manuka honey (MH) have a significant anticancer effect on breast cancer SD rat model (Ahmed et al, 2017). Our present study has been designed for the first time to do a detail analysis and comparison of the pattern of histological alterations in honey-treated MNU induced breast cancer in female SD rats with that of the non-treated ones.…”
Section: Introductionmentioning
confidence: 99%